Consumer Behavior in Marketing in The Digital EDGE - Zahid Hussain (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2023)
Digitization must have altered business and customer communication mechanisms, opening up new opportunities and lowering transaction costs. Moreover, digitalization, particularly e-commerce, is critical to the market's development because it facilitates the process relationships between users and vendors in multiple places. Digitalization is indeed probable to have overall economic advantages in the form of innovation and research, creative thinking, but also acquiring knowledge, as well as immediate and unrestricted exposure to sources of information and lower transactional indirect impacts. The objective of this research would be to look at consumer behaviour in the digital era and lead to a better understanding of digital marketing techniques, their effects on consumer behaviour and attitude, as well as start-ups like mobile apps, also resulting in effectiveness.